Erratum to ‘‘Photostability studies on gemifloxacin and lomefloxacin in bulk powder and dosage forms” [Eur. J. Chem. 5 (1) (2014) 73-80] - Tammam, Marwa Hosny (European Journal of Chemistry, 2014)
Erratum to ‘‘Photostability studies on gemifloxacin and lomefloxacin in bulk powder and dosage forms” [Eur. J. Chem. 5 (1) (2014) 73-80].